High Intensity Focused Ultrasound: Terapi Non-Invasif Efektif untuk Hipertensi Resisten - Rizki Arisandi (Jurnal Kedokteran Meditek, 2020)
Resistant hypertension is defined as blood pressure (BP) remaining above therapy goal despite the use of three or more antihypertensive drugs at maximally tolerated doses (one ideally being a diuretic) or BP that requires four or more agents to reach the blood pressure therapy goal. One approach used to treat resistant hypertension is renal denervation. Various methods have been developed, from the resection, Radiofrequency Ablation (RFA) catheter, to High-Intensity Focused Ultrasound (HIFU). HIFU is the newest method and has promising efficacy. The results of test in animal and clinical trial in humans are showing a good outcome. Moreover, HIFU is a non-invasive procedure so that able to minimize the undesirable effect of invasive or surgical procedure. The only reported side effect of this procedure is back pain which can be cured with painkiller medications.